State-specific cigarette use rates among service members and veterans, United States, 2017 - McDaniel, Justin T. (Tob Prev Cessat, 2019)
INTRODUCTION: Little is known about the geographical distribution of cigarette use among military service members and veterans. In this study, we estimated state-specific rates of current cigarette use for service members and veterans and compared these to the current cigarette use rates of civilians. METHODS: We used data from the 2017 Behavioral Risk Factor Surveillance System to generate survey-weighted percentages with 95% confidence intervals of current cigarette use among service members and veterans (SMVs) and civilians. Respondents (n=450016) were classified as an SMV if they answered in the affirmative to the following question: ‘Have you ever served on active duty in the United States Armed Forces, either in the regular military or in a National Guard or military reserve unit?’. Current cigarette users were persons who reported having smoked 100 cigarettes in their lifetime and smoked ‘some days’ or ‘every day’ at the administration of the survey. RESULTS: Nationally, 17.3% (95% CI: 16.6–18.0) of SMVs reported current cigarette use, while 16.2% (95% CI: 16.0–16.5) of civilians reported current cigarette use. By state, current cigarette use rates ranged from 10.0% in Utah (95% CI: 7.5–12.5) to 23.7% in Indiana (95% CI: 20.9–26.5) among service members and veterans, and from 8.8% in Utah (95% CI: 8.0–9.6) to 27.0% in West Virginia (95% CI: 25.3–28.6) among civilians. CONCLUSIONS: Resources and interventions directed at cigarette smoking cessation should consider military status and geography when recruiting participants.